2012
DOI: 10.5348/ijbti-2012-8-oa-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effectiveness of transfusion program in dengue patients receiving platelet transfusion

Abstract: Aims: Dengue infection is a global health problem affecting an estimated population of 50–100 millions every year. Thrombocytopenia is an essential diagnostic criteria. Platelet transfusion is given in those patients who have haemorrhagic manifestations along with thrombocytopenia. The aim of the study was to know the effectiveness of platelet transfusion in dengue patients. Methods: The study was conducted during the epidemic of dengue fever from July 2011 to October 2011. Serologically confirmed dengue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…All these patients had platelet counts less than 50,000 cells/mm 3 . This finding is in conjunction with another study by Kulkarni et al 5 They also noticed that sixty nine percentage of the haemorrhagic manifestations occurred in patients with severe thrombocytopenia.…”
Section: Maternal Outcomessupporting
confidence: 88%
“…All these patients had platelet counts less than 50,000 cells/mm 3 . This finding is in conjunction with another study by Kulkarni et al 5 They also noticed that sixty nine percentage of the haemorrhagic manifestations occurred in patients with severe thrombocytopenia.…”
Section: Maternal Outcomessupporting
confidence: 88%
“…[8] Reported rates of hemorrhagic manifestations in Indian studies vary between 6 and 37%. [9101112] Our study had a higher prevalence of severe dengue cases (11%) compared to that reported by Souza et al . (7.6%).…”
Section: Discussionmentioning
confidence: 47%
“…[9] However, the rate of platelet transfusion in our study (7.2%) was much lesser than the rate of 20–51% reported in other studies. [101112] In our hospital, platelet transfusion was given only with significant bleeding or for therapeutic interventions such as obtaining a central venous access or performing a gastroscopy. However, in many places, platelets are transfused not based on medical rationale, but as a response to an intense social pressure on the treating physicians by the patients or their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Inappropriate platelet transfusions in absence of bleeding have been reported from 13% to as high as 56.2% by various authors. [ 38 39 40 ] A study conducted in four tertiary level hospitals of Delhi observed that 73.5% of patients with dengue hemorrhagic fever and 48.7% of dengue fever classified as per WHO guidelines were given platelet transfusions. [ 41 ] Sugianto et al .…”
Section: P Latelet T Ransfusionsmentioning
confidence: 99%